Molecular cloning, over expression, and activity studies of a peptidic HIV-1 protease inhibitor: designed synthetic gene to functional recombinant peptide - Vathipadiekal, Vinod; Umasankar, Perunthottathu K.; Patole, Milind S.; Rao, Mala (Peptides, 2010)
The aspartic protease inhibitor (ATBI) purified from a Bacillus sp. is a potent inhibitor of several proteases including recombinant HIV-1 protease, pepsin, and fungal aspartic protease. In this study, we report the cloning, and over expression of a synthetic gene coding for ATBI in Escherichia coli and establish a purification Protocol. The ATBI molecule consists of eleven amino acids and is peptidic in nature. We used the peptide sequence data of ATBI to synthesize complementary oligonucleotides, which were annealed and subsequently cloned in-frame with the gene for glutathione-S-transferase (GST). The expression of the resulting fusion protein was induced in E. coli BL21-A1 cells using arabinose. The recombinant peptide was Purified using a reduced glutathione column, and cleaved with Factor Xa to remove the GST tag. The resultant product was further purified to homogeneity using RP-HPLC. Mass spectroscopy analysis revealed that the purified peptide had a molecular weight of 1186 Da which matches the theoretical molecular weight of the amino acids present in the synthetic gene. The recombinant peptide was found to be active in vitro against HIV-1 protease, pepsin, and fungal aspartic protease. The protocol described in this study may be used to clone pharmaceutically important peptide molecules. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Gateway cloning; HIV-1 protease; inhibitor; Proteases; Synthetic gene

Microbial production of xylitol from D-xylose and sugarcane bagasse hemicellulose using newly isolated thermotolerant yeast Debaryomyces hansenii - Prakash, Gyan; Varma, Anjanikumar; Prabhune, Asmita; Shouche, Yogesh; Rao, Mala (Bioresource Technology, 2011)
A thermotolerant yeast capable of fermenting xylose to xylitol at 40 C was isolated and identified as a strain of Debaryomyces hansenii by ITS sequencing. This paper reports the production of xylitol from D-xylose and sugarcane bagasse hemicellulose by free and Ca-alginate immobilized cells of D. hansenii. The efficiency of free and immobilized cells were compared for xylitol production from D-xylose and hemicellulose in batch culture at 40 degrees C. The maximum xylitol produced by free cells was 68.6 g/L from 100 g/L of xylose, with a yield of 0.76 g/g and volumetric productivity 0.44 g/L/h. The yield of xylitol and volumetric productivity were 0.69 g/g and 0.28 g/L/h respectively from hemicellulosic hydrolysate of sugarcane bagasse after detoxification with activated charcoal and ion exchange resins. The Ca-alginate immobilized D. hansenii cells produced 73.8 g of xylitol from 100 g/L of xylose with a yield of 0.82 g/g and volumetric productivity of 0.46 g/L/h and were reused for five batches with steady bioconversion rates and yields. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Immobilization; Sugarcane bagasse hemicellulose; Thermotolerant Debaryomyces hansenii; xylitol; Xylose

Mechanistic insights into the inhibition of endo-beta 1,4 xyloglucan hydrolase by a classical aspartic protease inhibitor - Menon, Vishnu; Rao, Mala (Journal of Fluorescence, 2013)
This is the first report of inactivation of xyloglucanase from Thermomonospora sp by pepstatin A, a specific inhibitor towards aspartic proteases. The steady state kinetics revealed a reversible, competitive, two-step inhibition mechanism with IC (50) and K (i) values of 3.5 +/- 0.5 mu M and 1.25 +/- 0.5 mu M respectively. The rate constants determined for the isomerization of EI to EI* and the dissociation of EI* were 14.5 +/- 1.5 x 10(-5) s(-1) and 2.85 +/- 1.2 x 10(-8) s(-1) respectively, whereas the overall inhibition constant K (i) (*) was 27 +/- 1 nM. The conformational changes induced upon inhibitor binding to xyloglucanase were monitored by fluorescence analysis and the rate constants derived were in agreement with the kinetic data. The abolished isoindole fluorescence of o-phthalaldehyde (OPTA)-labeled xyloglucanase and far UV analysis suggested that pepstatin binds to the active site of the enzyme. Our results revealed that the inactivation of xyloglucanase is due to the interference in the electronic microenvironment and disruption of the hydrogen-bonding network between the essential histidine and other residues involved in catalysis.
Keywords: 4 xyloglucan hydrolase; Endo-beta 1; Enzyme kinetics; Inactivation mechanism; Pepstatin; Slow-tight binding